Enhanced photocatalytic properties of ZnFe2O4-doped ZnIn2S4 heterostructure under visible light irradiation. Issue 86 (1st September 2016) - Yang, Wu; Chen, Dezhi; Quan, Hongying; Wu, Shaolin; Luo, Xubiao; Guo, Lin
Abstract : ZnFe2 O4 -doped ZnIn2 S4 heterostructure was fabricated and showed enhanced photocatalytic performance under visible light irradiation. Abstract : ZnFe2 O4 -doped ZnIn2 S4 heterostructures were fabricated with a series of different proportions of ZnFe2 O4 using a two-step solvothermal method. The as-synthesized ZnFe2 O4 –ZnIn2 S4 heterostructure exhibited enhanced photocatalytic performance in the degradation of organic pollutants compared to bare ZnIn2 S4 and ZnFe2 O4 under visible light irradiation, and the 2.5 wt% ZnFe2 O4 –ZnIn2 S4 showed the highest activity. The enhanced mechanism of photocatalytic activity can be mainly attributed to the stable heterojunction interface between ZnFe2 O4 and ZnIn2 S4, which can efficiently improve the separation of photogenerated carriers. Meanwhile, the increased surface-active sites and extended light absorption of ZnIn2 S4 after the decoration of ZnFe2 O4 nanoparticles may also play a certain role in enhancing photocatalytic activity.